EPSA, an Umbrella Organisation of all European Pharmaceutical Students’ Associations - Sousa, Khatriny (FarmaJournal, 2023)
In this session it was presented the different Students Associations (ASEF, FEEF and EPSA) and I had the pleasurer to present EPSA and our projects. EPSA is the European Pharmaceutical’s Students Association, and we represent more than 100 000 (one hundred thousand) students in 35 European Countries. EPSA mission is to engage with the students bringing Pharmacy, Knowledge, and Students together, promoting a personal and professional development. We have 4 big events during the year: Annual Reception (takes place in Brussels); the Annual Congress; Autumn Assembly, and the Summer University, where the participants can develop their soft and hard skills. EPSA promotes advocacy and the concerns and opinion of the European Pharmacy Students regarding the Digital Health, the Pharmaceutical Curricula, and other different topics.